2021
DOI: 10.1111/evo.14211
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary implications of dental anomalies in bats

Abstract: The gain or loss of anatomical features is an important mechanism of morphological evolution and ecological adaptation. Dental anomalies—the loss or gain of teeth—are widespread and a potential source of craniodental specialization among mammals, yet their macroevolutionary patterns have been rarely explored. We present the first phylogenetic comparative study of dental anomalies across the second largest mammal Order, Chiroptera (bats). We conducted an extensive literature review and surveyed a large sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…This emphasizes the importance of understanding trait evolution in bats and optimizing the selection of traits that have often been neglected despite their importance. The majority of the previous evolutionary trait studies on bats focus on skulls and dentition (Jacobs et al, 2014; Clavel & Morlon, 2020; Esquivel et al, 2021; Giacomini et al, 2021), but few studies have been focussed on measuring the noseleaf traits, particularly in Old‐World bats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the importance of understanding trait evolution in bats and optimizing the selection of traits that have often been neglected despite their importance. The majority of the previous evolutionary trait studies on bats focus on skulls and dentition (Jacobs et al, 2014; Clavel & Morlon, 2020; Esquivel et al, 2021; Giacomini et al, 2021), but few studies have been focussed on measuring the noseleaf traits, particularly in Old‐World bats.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the evolution of phenotypic traits in bats is clearly in the preliminary stages. Nevertheless, previous studies have shown interesting findings on the evolutionary relationship among morphological traits, echolocation, ecological demands, functional traits, and bat behavior (i.e., Jacobs et al, 2014; Brokaw & Smotherman, 2020; López‐Cuamatzi et al, 2020; Esquivel et al, 2021). Yet, gathering complex data for greater systematic sampling to achieve robust results on these inter‐relationships remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…as environmental instability (Chemisquy & Martin 2016), limited gene flow (Martin 2013), atavisms (Hall 2010), or even aleatory mutations (Hauer 2002). At least for bats, the phylogenetic structure in the occurrence of dental anomalies indicates that some shared processes among related species are also influencing the phenomenon (Esquivel et al 2021). The main types of dental anomalies described for the order Chiroptera are hypodontia (the absence of teeth), and polyodontia (the presence of supernumerary teeth) (Esquivel et al 2021).…”
mentioning
confidence: 99%
“…At least for bats, the phylogenetic structure in the occurrence of dental anomalies indicates that some shared processes among related species are also influencing the phenomenon (Esquivel et al 2021). The main types of dental anomalies described for the order Chiroptera are hypodontia (the absence of teeth), and polyodontia (the presence of supernumerary teeth) (Esquivel et al 2021). The etiologies of these abnormal morphologies, however, are not fully comprehended.…”
mentioning
confidence: 99%
See 1 more Smart Citation